PENGARUH SINETRON TELEVISI DAN FILM TERHADAP PEREKMBANGAN MORAL REMAJA - Carmia Diahloka (Universitas Tribhuwana Tunggadewi, 2012)
Advanced stage of education or senior high school and vocational school is the potentially institution if the students are researched further because the teenagers in advanced stage of education has more difficulty in their transition period. The teenagers have to get special attention, so that the research will find out how much the influence appears as the consequence of watching television, especially for the moral development of teenagers. The involvement and the role of electronic mass media, especially television, made the researcher curious more about the influence of the entertainment program of television, for instance series drama and movie. Furthermore, the researcher wanted to find out: is there any effect from series drama variable in television and movie to the moral development of teenagers, which one perhaps has dominant effect between series drama variable in television and movie variable to the moral development of teenagers. This research goal was want to find out the effect of series drama in television and movie to the moral development of teenagers, and which one has dominant effect between drama series in television and film in television to the moral development of teenagers.